The incidence of Trichomonas vaginalis infection in women attending nine sexually transmitted diseases clinics in the USA. (12th June 2015) - Alcaide, Maria L; Feaster, Daniel J; Duan, Rui; Cohen, Stephanie; Diaz, Chanelle; Castro, Jose G; Golden, Matthew R; Henn, Sarah; Colfax, Grant N; Metsch, Lisa R
Abstract : Objectives: Trichomoniasis (TV) is associated with an increased risk of acquisition of sexually transmitted diseases (STDs) and HIV. The purpose of this study is to evaluate factors associated with incidence TV among female STD clinic attendees in the USA. Methods: Data were collected from women participating in a randomised controlled trial evaluating brief risk reduction counselling at the time of HIV testing to reduce sexually transmitted infections (STIs) incidence in STD clinics. Participants recruited from STD clinics underwent STI testing at baseline and 6-month follow-up. TV testing was performed using Nucleic Acid Amplification Test. Results: 1704 participants completed study assessments. Prevalence of TV was 14.6%, chlamydia 8.6%, gonorrhoea 3.0%, herpes simplex virus 2 44.7% and HIV 0.4%. Cumulative 6-month incidence of TV was 7.5%. Almost 50% of the incident TV cases had TV at baseline and had received treatment. Factors associated with incidence of TV were having chlamydia, TV and HIV at baseline: TV relative risk (RR)=3.37 (95% CI 2.35 to 4.83, p<0.001); chlamydia RR=1.92 (95% CI 1.23 to 2.99, p=0.04); and HIV=1.59 (95% CI 1.01 to 2.50, p=0.047). Conclusions: Prevalent and incident TV is common among STD clinic attendees; and baseline TV is the main risk factor for incident TV, suggesting high rates of reinfection or treatment failures. This supports the importance of rescreening women after treatment for TV, evaluating current treatment regimens and programmes to ensure treatment of sexual partners. Clinical trial number: NCT01154296.